The impact of domicile on validity of will : research on Malaysian women with foreign spouse from United Kingdom, Singapore and Indonesia / Noraini Ismail, Norazlina Abdul Aziz and Zuramaznum Sainan - Ismail, Noraini; Abdul Aziz, Norazlina; Sainan, Zuramaznum (Institute of Research, Development and Commercialization, Universiti Teknologi MARA, 2008)
Colonial era has left an impact to Malaysian culture. Marriage is one of the ways that the invader had used in starting their plan of invasion. Nowadays, after 48 years of independence, the scenario of local women with foreign spouse has been an accepted culture in this country. In the name of love, the marriage was solemnized with no regards to the future undertakings. One of the problems that arose if the marriage ends with dispute and leads to process of divorce is on the distribution of properties upon death. This involves interference of conflict of laws. One of the important facts that need to be pondering upon is the determination of the testatrix's domicile. Other important elements are the location of the properties either it be lex domicile or lex situs. As Malaysian Law is silent on the interpretation of domicile, according to Section 3(1) of Civil Law Act 1956, we will follow the rule of common law. Under the common law, a husband and wife were viewed as one entity. Only a decree of divorce will release her from this dependence. The question on the validity of will executed by deceased spouse is very much related to the domicile of the parties involve. It is still an unresolved issue whether the law of the deceased country or law of the widow country should administer it. This will invite the intrusion of law in settlement of case. Spouse from different country, have different set of law. The law, which they are bound to, depends on the country of their domicile. As for women, once they entered the marriage relation, the domicile will follow their husband's domicile, which is known as domicile of dependent. This research will focus on the problem arose and suggestion of solution in determining the administration of a will and rules of succession.